2016
DOI: 10.1111/jan.13163
|View full text |Cite
|
Sign up to set email alerts
|

Theory‐based self‐management educational interventions on patients with type 2 diabetes: a systematic review and meta‐analysis of randomized controlled trials

Abstract: To get theory-based interventions to produce more effects, the role of patients should be more involved and stronger and the education team should be trained beyond the primary preparation for the self-management education program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 73 publications
4
84
0
Order By: Relevance
“…Our nonsignificant HbA 1c findings are in line with the 2.5-year follow-up findings from another Dutch lifestyle programme [21], the 3-year follow-up findings of the DESMOND study [7] and those of a meta-analysis that included four studies with a follow-up of between 12 and 18 months [HbA 1c mean difference of -0.1% (95% CI -0.3 to 0.1)] [22]. This is in contrast to three systematic reviews and the Look Ahead programme that showed a significant decrease in HbA 1c in favour of the self-management/lifestyle group, with mean differences ranging from -0.27 to -0.87%, the effect being smaller after longer follow-up [23][24][25][26]. The lack of change in the present study might be partly attributable to excellent baseline values.…”
Section: Discussionmentioning
confidence: 99%
“…Our nonsignificant HbA 1c findings are in line with the 2.5-year follow-up findings from another Dutch lifestyle programme [21], the 3-year follow-up findings of the DESMOND study [7] and those of a meta-analysis that included four studies with a follow-up of between 12 and 18 months [HbA 1c mean difference of -0.1% (95% CI -0.3 to 0.1)] [22]. This is in contrast to three systematic reviews and the Look Ahead programme that showed a significant decrease in HbA 1c in favour of the self-management/lifestyle group, with mean differences ranging from -0.27 to -0.87%, the effect being smaller after longer follow-up [23][24][25][26]. The lack of change in the present study might be partly attributable to excellent baseline values.…”
Section: Discussionmentioning
confidence: 99%
“…Much more evidence is available regarding the efficacy of DSME in type 2 than in type 1 diabetes. We identified 21 meta‐analyses on the efficacy of DSME in type 2 diabetes, which included more than 450 primary studies with a combined total of >74 000 participants . The meta‐analytical studies reported results on different follow‐up periods (Table ), which ranged from 1 to 24 months.…”
Section: What Has the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…Scores range from 0 to 27 and are classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [16,17]. Scores range from 0 to 27 and are classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [16,17].…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…The PHQ-9 evaluates depressive symptoms and grades the severity of depression. Scores range from 0 to 27 and are classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [16,17].…”
Section: Depressive Symptomsmentioning
confidence: 99%